2010
DOI: 10.1007/s00405-010-1367-z
|View full text |Cite
|
Sign up to set email alerts
|

Fasciocutaneous free flap reconstruction for squamous cell carcinoma of the hypopharynx

Abstract: The purpose of this study was to examine functional and surgical outcomes after fasciocutaneous free flap reconstruction of the hypopharynx. A retrospective review of the records of 48 consecutive patients that underwent hypopharyngectomy and reconstruction using fasciocutaneous free flaps between 1996 and 2009 was performed. Flap donor sites included the radial forearm (n = 42), anterolateral thigh (n = 5), and lateral thigh (n = 1). There was no perioperative mortality, and the free flap survival rate was 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Our overall flap failure rate was 12 %, with a slightly higher flap failure rate in the pedicled flap group than the free flap group (13 versus 11 %). When we compare this with other studies, combined flap failure rates varies from 0 to 9.5 % [ 1 , 13 , 17 , 19 21 ]. Pedicled pectoralis major often has a failure rate of 0 %, because there is no need for microvascular anastomosis [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 82%
“…Our overall flap failure rate was 12 %, with a slightly higher flap failure rate in the pedicled flap group than the free flap group (13 versus 11 %). When we compare this with other studies, combined flap failure rates varies from 0 to 9.5 % [ 1 , 13 , 17 , 19 21 ]. Pedicled pectoralis major often has a failure rate of 0 %, because there is no need for microvascular anastomosis [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 82%
“…With the development of microsurgical techniques, several fasciocutaneous free flaps from the radial forearm and anterolateral thigh have been widely utilized for the reconstruction of the hypopharynx [4]. Among the many free skin flaps available the radial forearm flap, which was first reported to be used for pharyngoesophageal reconstruction in 1985 [5], is the most popular free flap for head and neck soft tissue reconstruction after tumor extirpation.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the average time to achieve oral re-alimentation was 23.0 days postoperatively. [ 22 ] In this study, the average recovery time of eating function in the 2 groups was 17.3 days and 23.1 days, respectively. This meant that the xeno-ADM graft was conducive in restoring eating function, and assists in quickly restoring the postoperative quality of life.…”
Section: Discussionmentioning
confidence: 61%